1 KOMPOSISI TANAH KARO DALAM SIMFONI - Andi Alexander (Saraswati)
Karo tribe is a part of Batak tribes family which settled down in middle and west part of the Province of North Sumatra, Indonesia. The other tribes of  Batak tribes family are Angkola, Mandailing, Toba, Dairi/Pak-pak, dan Simalungun tribe. Like the other Indonesian traditional music, Karonese traditional music has a distinctive characteristic like the musical unsure and instrumentation. Karonese traditional music has a potential to be develop into another nuance or form. The work Tanah Karo Dalam Simfoni (Karo Land in Symphony) is a piece that combine the musical principles of western music, like form, harmony, and orchestration with the principles of Karonese traditional music like scale, ornamentation, and rhythm. This work has the symphony form that consist of three movements. The first movement has brilliance nuance in tempo Allegro, the second movement has sad nuance in tempo adagio, and third or last movement has happy and cheerful nuance with more Karonese traditional music influence in tempo allegro. This work is be played by orchestra and Karonese traditional music ansamble.   Keywords: Karo Land, Symphony, Orchestra